(untitled) (Universal International Scientific Journal, 2026)
Legends are closely connected with history; however, unlike historical records, they are not fixed to exact dates. Instead, they develop gradually over long periods of time. Most legends begin as oral traditions and are later recorded in written form. Both English and Uzbek legends trace their origins to ancient and medieval centuries, although they continued to evolve in later historical periods